DIAGENETIC ALTERATIONS OF COPPER SULFIDES IN MODERN ORE-BEARING SEDIMENTS OF THE LOGATCHEV-1 HYDROTHERMAL FIELD (MID-ATLANTIC RIDGE 14°45′ N) - Gablina I.F.; Gor'kova N.V.; Semkova T.A.; Stepanova T.V. (My University, 2006)
Sulfide ore samples recovered by corers from and beyond Orebody 1 in the Logatchev-1 hydrothermal field (Mid-Atlantic Ridge, 14°45′ N) are studied by optical, electron microscopic, X-ray microspectral, and X-ray diffraction methods. The major and ore minerals are identified. Sulfides of the Cu-S system, the major ore-forming minerals in sediments, are investigated in detail. Specific features of their composition, structure, secondary alterations, and distribution in sediments of the Logatchev-1 field are considered. It has been established that sulfide concretions in modern sediments primarily consist of nonstoichiometric minerals of the chalcocite-digenite series, i.e., djurleite (Cu1.96S) and roxbyite (Cu1.75-1.86 S). It is assumed that copper sulfides primarily precipitated from hydrothermal solutions as high-temperature hexagonal chalcocite that was replaced after the hydrothermal activity by djurleite, roxbyite, and other nonstoichiometric minerals of the Cu-S system. Based on the comparison of their paragenetic associations with those of copper sulfides in hydrothermal chimneys, the paper discusses constraints of the diagenetic transformation of sulfides in ore-bearing sediments and the halmyrolysis of modern hydrothermal edifices located in contact with seawater. Roxbyite recently discovered in oceanic sediments plays a specific role in these processes. © Pleiades Publishing, Inc. 2006.